2009
DOI: 10.1007/s00199-009-0448-y
|View full text |Cite
|
Sign up to set email alerts
|

Computing equilibria: a computational complexity perspective

Abstract: Computational complexity is the subfield of computer science that rigorously studies the intrinsic difficulty of computational problems. This survey explains how complexity theory defines "hard problems"; applies these concepts to several equilibrium computation problems; and discusses implications for computation, games, and behavior. We assume minimal prior background in computer science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 132 publications
0
45
0
Order By: Relevance
“…In a spectacular sequence of papers (summarized in Daskalakis, Goldberg, andPapadimitriou 2006, andChen andDeng 2006), it was recently shown that this problem is "PPAD-complete", that is, in a certain sense "as hard" as solving many other, seemingly harder, problems related to equilibria, for example finding an approximate fixed point of a Brouwer function. In his contribution, Roughgarden (2010) explains this result and many others.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…In a spectacular sequence of papers (summarized in Daskalakis, Goldberg, andPapadimitriou 2006, andChen andDeng 2006), it was recently shown that this problem is "PPAD-complete", that is, in a certain sense "as hard" as solving many other, seemingly harder, problems related to equilibria, for example finding an approximate fixed point of a Brouwer function. In his contribution, Roughgarden (2010) explains this result and many others.…”
mentioning
confidence: 63%
“…This is important, for example, for applications in artificial intelligence where a poker playing program should exploit mistakes of an opponent who does not play optimally. Tim Roughgarden's survey (Roughgarden 2010) is directed at readers with a background in economics. Computational complexity deals with the intrinsic difficulty of solving a computational problem.…”
mentioning
confidence: 99%
“…However, new results suggest that there is no general polynomial time approximation scheme for computing a Nash equilibrium [10]. For recent surveys on the problem of computing Nash equilibria, one can refer to [14,42]. A comprehensive survey of various methods of computing Nash equilibria and their computational complexity results are given in [34].…”
Section: Rational Interactions and Strategic Equilibriummentioning
confidence: 98%
“…We then discuss the key differences between the two settings. For work on the complexity of computing other equilibrium concepts, such as market, correlated, and approximate Nash equilibria, and for a discussion of equilibrium computation in extensive-form, compact, randomly generated, and stochastic games, see [30, Part I] and [38] and the references therein.…”
Section: Complexity Of Equilibrium Computationmentioning
confidence: 99%